HUBUNGAN PROFESIONALISME DAN KOORDINASI DENGAN EFEKTIVITAS KERJA PERSONEL KEUANGAN MARKAS KOMANDO AKADEMI MILITER N.A.2.06.02. - Tri Wahyuni (JMAN (Jurnal Mahasiswa Administrasi Negara), 2018)
The research study examined three concepts ; effectiveness of work, profesionalism of work, and coordination of work. Profesionalism and coordination are independent variable, while effectiveness is dependent variable. This research was conducted in 34 financial employee of Markas Komando Akademi Militer N.A.2.06.02.The methodology of this research was quantitative research. The method of collecting data were observation, interview,and questionnaire. This research was included in population research as the population were34 employee. Before the writer conducted the research, the writer had conducted validity test and reability test. Then the writer also did linearity test and multicollinearity test. The technique of data analysis in this research were product moment correlation and multiple correlation analysis. The result of first hypothesis showed rhitung  (0,645) > rtabel  (0,339), so there was a significant correlation between professionalism of work (X1) and effectiveness of work (Y) in 34 financial employee of Markas Komando Akademi Militer N.A.2.06.02. The result of second hypothesis showed rhitung (0,659) > rtabel (0,339). Hence H0 was accepted and Ha was refused so there was a significant correlation between coordination (X2) and effectiveness of work (Y) in 34 financial employee of Markas Komando Akademi Militer N.A.2.06.02. The result of third hypothesis showed that there was a positive and significant correlation between professionalism of work and coordination work together with effectiveness of work in 34 financial employee of Markas Komando Akademi Militer N.A.2.06.02. It was proven by determination coefficient (R2) ; 0,533 and regression ; Fregression  17,702. The contribution of effectiveness of work simultaneously ; 53,30% while 46,70% was determined by other variables. The percentage of effectiveness of 34 financial employee of Markas Komando Akademi Militer N.A.2.06.02. was often 39,47%. Key words : effectiveness of work, profesionalism of work,coordination of work